Transcriptional profiling of Bordetella pertussis reveals requirement of RNA chaperone Hfq for Type III secretion system functionality - Bibova, Ilona; Hot, David; Keidel, Kristina; Amman, Fabian; Slupek, Stephanie; Cerny, Ondrej; Gross, Roy; Vecerek, Branislav (RNA biology, 2015)
Bordetella pertussis, the causative agent of human whooping cough (pertussis) produces a complex array of virulence factors in order to establish efficient infection in the host. The RNA chaperone Hfq and small regulatory RNAs are key players in posttranscriptional regulation in bacteria and have been shown to play an essential role in virulence of a broad spectrum of bacterial pathogens. This study represents the first attempt to characterize the Hfq regulon of the human pathogen B. pertussis under laboratory conditions as well as upon passage in the host and indicates that loss of Hfq has a profound effect on gene expression in B. pertussis. Comparative transcriptional profiling revealed that Hfq is required for expression of several virulence factors in B. pertussis cells including the Type III secretion system (T3SS). In striking contrast to the wt strain, T3SS did not become operational in the hfq mutant passaged either through mice or macrophages thereby proving that Hfq is required for the functionality of the B. pertussis T3SS. Likewise, expression of virulence factors vag8 and tcfA encoding autotransporter and tracheal colonization factor, respectively, was strongly reduced in the hfq mutant. Importantly, for the first time we demonstrate that B. pertussis T3SS can be activated upon contact with macrophage cells in vitro.
Keywords: bakteriální RNA; transkriptom; Host-Pathogen Interactions; Cell Line; infection; ABC protein, ATP-binding cassette protein; Host Factor 1 Protein; Virulence Factors, Bordetella; RT-qPCR, quantitative reverse transcription polymerase chain reaction; Bacterial Proteins; virulence; P, P-value; Transcriptome; wt, wild-type; SS medium, Steiner-Scholte medium; regulace genové exprese u bakterií; stanovení celkové genové exprese; Regulon; Gene Expression Profiling; Bordetella pertussis; Hfq; T3SS, Type III secretion system; Type V Secretion Systems; Animals; Type III Secretion Systems; OMP, outer membrane protein; interakce hostitele a patogenu; zvířata; T3SS; makrofágy; bakteriální proteiny; myši; buněčné linie; transcriptomics; infekce bakteriemi rodu Bordetella; CFU, colony forming unit; sekreční systém typu III; regulon; sekreční systém typu V; protein hostitelského faktoru 1; Macrophages; Mice; RNA, Bacterial; Bordetella Infections; Bsp22; faktory virulence rodu Bordetella; Gene Expression Regulation, Bacterial